DIAGNOSTICS OF PERSONALITY PROFESSIONAL ORIENTATION: GERMAN EXPERIENCE - Krystopchuk, Tatiana (Continuing Professional Education: Theory and Practice, 2019)
In the article the structural elements of professional orientation of youth (professional diagnostics, professional education, professional consultation, professional selection, professional adaptation) are substantiated. The purpose of diagnostics of personality professional orientation, which is the study of interests, needs, abilities, professional intentions and professional orientation of the individual is discovered with the help of a questionnaire and test methods. It is determined that one of the factors of the lowest level of German youth unemployment among the EU countries is dual professional education, which is focused on the practical needs of youth, provides employment and achieving of professional competence in the enterprise and promotes motivation. The basic elements and types of dual professional education in Germany are outlined. The general description of the main types of professional education (professional training in enterprises, improvement or certification training, retraining) is submitted. It is determined the objectives of youth professional orientation in Germany. The program of professional orientation and the model of youth transition from school to profession, based on young people consultancy about career choice and practical training is presented. The stages of realisation of the youth professional orientation program (analysis of potential, opportunity to test themselves in different occupations (visiting workshops); the work of class teachers and social workers with students on professional orientation).